2022
DOI: 10.1002/alz.12629
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment among rural‐dwelling older adults in China: A community‐based study

Abstract: Background: Epidemiological studies of mild cognitive impairment (MCI) and subtypes of MCI have rarely focused on rural residents in China. Methods:This population-based study included 5068 participants (age ≥60 years) who were living in rural communities. We defined MCI, amnestic MCI (aMCI), and nonamnestic MCI (naMCI) following the Petersen's criteria that integrated neuropsychological assessments with in-person clinical evaluations. Results:The overall prevalence of MCI, aMCI, and naMCI was 26.48%, 22.30%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 53 publications
0
53
0
Order By: Relevance
“…The prevalence of MCI in rural areas has been reported to be as high as over 26% [ 24 ], making its study in the rural context relevant and the investigation of the factors that may be associated with cognitive decline in those areas important. This review aimed to summarize the latest research on the differences between rural- and urban-dwelling older adults with MCI.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MCI in rural areas has been reported to be as high as over 26% [ 24 ], making its study in the rural context relevant and the investigation of the factors that may be associated with cognitive decline in those areas important. This review aimed to summarize the latest research on the differences between rural- and urban-dwelling older adults with MCI.…”
Section: Discussionmentioning
confidence: 99%
“…This population-based cross-sectional study used data collected from participants in the baseline examination of the Multimodal Interventions to Delay Dementia and Disability in rural China (MIND-China) in Yanlou Town, Yanggu County in Shandong Province, conducted by Shandong Provincial Hospital in collaboration with the Yanlou Town Health Center. As a participating project in the World-Wide FINGERS Network (a global network for dementia risk reduction and prevention) [16], MIND-CHINA was aimed to test the effects of multidomain interventions (e.g., lifestyle and nutritional guidelines, physical exercise, cognitive training, and improvement in the management of major cardiovascular risk factors) on cognitive decline and onset of dementia and disability among rural-dwelling elderly people [17]. MIND-China targeted older adults who were aged 60 years or older and living in the 52 communities (villages) in Yanlou Town.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…China has a low prevalence of knowledge of dementia, which is viewed as a normal part of the aging process, and the behavioral and cognitive symptoms of dementia are attributed to mental illnesses ( Liu et al, 2008 ). A recent study showed that more than a quarter of the rural elderly in China is at a high risk of dementia ( Cong et al, 2022 ). However, dementia has not yet received enough attention at the national level in China, and a national strategic action plan for dementia has not been considered in the “Healthy China 2030” Plan and China’s Medium- and Long-term Plan for the Prevention and Treatment of Chronic Diseases (2017–2025) ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%